Biorenewable resources : engineering new products from agriculture - Brown, Robert C. (Robert Clinton); Brown, Tristan R. (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2014)
Biorenewable resources are the dedicated energy crops, agricultural residues, and organic wastes that serve as feedstocks in the production of fuels, chemicals, energy, and materials for the emerging bioeconomy. This edition provides an overview of the field that incorporates significant advances made in the field over the last decade. It is thoroughly revised and expanded to better serve the needs of students, professionals, and researchers working on the production and processing of biorenewable resources. Chapters provide grounding in fundamental concepts of engineering thermodynamics and organic chemistry relevant to the field, as well as provide practical guidance in feedstock production, processing, economics, and policy. --
Fundamental concepts in engineering thermodynamics -- Organic chemistry -- The biorenewable resource base -- Production of biorenewable resources -- Products from biorenewable resources -- Biochemical processing of carbohydrate-rich biomass -- Thermochemical processing of lignocellulosic biomass -- Processing of oleaginous biomass -- Processing of biorenewable resources into natural fibers -- Environmental impact of the bioeconomy -- Economics of biorenewable resources -- Biorenewable policy.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biomass energy; BUSINESS & ECONOMICS -- Real Estate -- General; Biomass energy; Electronic books; Electronic books